2012
DOI: 10.1371/journal.pone.0052224
|View full text |Cite
|
Sign up to set email alerts
|

Increased Feeding and Nutrient Excretion of Adult Antarctic Krill, Euphausia superba, Exposed to Enhanced Carbon Dioxide (CO2)

Abstract: Ocean acidification has a wide-ranging potential for impacting the physiology and metabolism of zooplankton. Sufficiently elevated CO2 concentrations can alter internal acid-base balance, compromising homeostatic regulation and disrupting internal systems ranging from oxygen transport to ion balance. We assessed feeding and nutrient excretion rates in natural populations of the keystone species Euphausia superba (Antarctic krill) by conducting a CO2 perturbation experiment at ambient and elevated atmospheric C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 109 publications
2
39
0
Order By: Relevance
“…Besides this krill decline, differences in the stoichiometry of excretion products are potentially important in determining the relative degree of nutrient limitation and thus algal species composition (Vanni 2002). It has been described that environmental changes can affect the ratios at which the different nutrients are recycled by krill, in example, predicting increased NH 4 + , DOC, and PO 4 + release rates in a high CO 2 scenario (Saba et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Besides this krill decline, differences in the stoichiometry of excretion products are potentially important in determining the relative degree of nutrient limitation and thus algal species composition (Vanni 2002). It has been described that environmental changes can affect the ratios at which the different nutrients are recycled by krill, in example, predicting increased NH 4 + , DOC, and PO 4 + release rates in a high CO 2 scenario (Saba et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that Euphausia superba, a keystone species in Antarctic ecosystems, has reduced hatching at 1250 µatm pCO 2 (pH 7.50) compared to 380 µatm and complete hatching failure at 2000 µatm pCO 2 (pH 7.36−7.40); however, at 3 d post hatch (dph) larval swimming activity is not affected at 1000 µatm pCO 2 (Kawaguchi et al 2011(Kawaguchi et al , 2013. Even at moderate levels of 672 µatm pCO 2 (pH 7.84), adult E. superba increase feeding and nutrient excretion rates, which may indicate shifts in metabolism associated with acid−base regulation (Saba et al 2012). Sub-adults of the north Atlantic krill Nyctiphanes couchii have reduced survival at pCO 2 concentrations between 1100 and 1700 µatm pCO 2 (pH 7.63 and 7.47), but other life stages have not been tested (Sperfeld et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adult behavioural changes, avoiding approximately 3.1d (Buchholz 2003). Krill IMP significantly lower at elevated temperature treatments (Brown et al 2010b;Saba et al 2012). production could deprive krill of sufficient food to support their energy requirements, and therefore retard krill gonadal development and spawning (Loeb et al 1997).…”
Section: Observed Impactmentioning
confidence: 93%
“…Ingestion rates of krill 3.5 times higher than krill ingestion rates at ambient, present day CO 2 concentrations (Saba et al 2012). Under the RCP 8.5 scenario most of krill habitat will suffer at least 20% lower hatching success by 2100, with reductions of up to 60-70% in the Weddell Sea (Sth Atlantic) = threshold of no recruitment at 2000 ppm CO 2 .…”
Section: Observed Impactmentioning
confidence: 97%
See 1 more Smart Citation